Shades of grey: the need for a multi-disciplinary approach to research investigating alcohol and ageing - Celia Wilkinson; Julie Dare (SAGE Publishing, 2014)
This paper calls for an increase in multi-disciplinary research on the issue of alcohol and ageing, to ensure public health interventions reflect the complex and diverse needs of older drinkers. Older people (65+ years) represent a unique segment of the population; compared to adolescents and younger people, they are more likely to have a range of co-morbid conditions and be taking prescribed medication, and are more physiologically vulnerable to the effects of alcohol. This suggests that from a public health perspective, alcohol use by older people is problematic. However, as with younger people, alcohol use is closely associated with socialisation and social engagement. While social engagement is important at all stages of life, it is particularly critical as people age, when many of the formal social roles which provide a catalyst for social integration shift or are lost. Currently, however, there is little evidence of an integrated public health response to the complex issue of alcohol and ageing. That is, what is needed is a concurrent acknowledgement of the health problems that may be associated with contraindicated alcohol use, versus the potential health benefits that can accrue from social drinking. This will require a holistic rather than reductionist approach that integrates biomedical and social science insights to develop a more comprehensive and nuanced understanding of the implications of alcohol use amongst diverse populations of older people.